Enamine‐Based Hydrophilic Dynamic Covalent Polymer Networks: Effects of pH, and Copolymer Composition and Concentration on the Aqueous Swelling Degrees and the Gel Formation Times. Issue 1 (18th December 2015) - Apostolides, Demetris E.; Hadjicosta, Argyro; Patrickios, Costas S.
Summary: In this work, we explore the formation in water of dynamic covalent polymer networks cross‐linked via enamine groups. The polymer networks resulted from the combination of pairs of chemically complementary hydrophilic statistical copolymers, synthesized via reversible addition‐fragmentation chain transfer polymerization, and bearing a primary amine group comonomer on the one hand, and acetoacetate groups on the other; the main comonomer in both statistical copolymers was poly(ethylene glycol) methacrylate methyl ether. In this preliminary investigation, the gel formation time and the equilibrium swelling degrees in water were measured at different pH values, different copolymer concentrations, and for different copolymers. It was found that the gel formation time was reduced as the copolymer concentration was increased, and as the contents in amine and acetoacetate units in the copolymers was increased; furthermore, a minimum in the gel formation time was observed at pH 8.0. The effect of these three factors on the equilibrium aqueous swelling degrees was found to be much weaker than on gel formation time.